Finding official British information : official publishing in the digital age - Inman, Jane (Chandos information professional series., 2012)
Covering central and local government, the devolved assemblies and other public bodies in the UK, this practical handbook is for the non-specialist. It details the different bodies which publish official material, describes the types of material published, how it is made available and how to find it.